Pragmatics in EFL teaching: how speech acts are addressed in a Brazilian textbook series - Tavares, Paulo Ott (BELT - Brazilian English Language Teaching Journal, 2014)
This paper aims at discussing and analyzing the approach to speech acts in an EFL textbook series used in Brazilian public schools. In order to do that, the concepts of pragmatics and pragmatic competence, as well as their implications to foreign language (FL) teaching, are discussed. Then, a brief review of the Speech Act Theory is presented. After describing the approach to FL teaching proposed by the PCNs and the selection of textbooks through the PNLD, we analyze one series, selected for the 2014-2016 triennium. The conclusion is that speech acts are not deeply approached, but that is in accordance with the goals of the series.